Dialectical behaviour therapy skills reconsidered: applying skills training to emotionally dysregulated individuals who do not engage in suicidal and self-harming behaviours - Mary Kells; Mary Joyce; Daniel Flynn; Ailbhe Spillane; Aoife Hayes (Borderline Personality Disorder and Emotion Dysregulation, 2020)
Abstract Background Dialectical behaviour therapy (DBT) is an evidence-based intervention for borderline personality disorder (BPD) but is an intensive treatment with significant health service costs. Access to DBT can sometimes be restricted due to limited resources. Positive results have been reported for the use of DBT skills training (DBT-ST), one of the four modes of standard DBT, in the treatment of individuals with BPD who self-harm. This study evaluates DBT-ST for a subgroup of individuals attending community mental health services who may have a diagnosis of BPD (or emerging BPD traits) but who are not actively self-harming. Methods Participants in this study were 100 adults attending community mental health services with a diagnosis of BPD, emerging BPD traits or emotion dysregulation who were not actively self-harming. The majority of participants were female (71%), aged 25–34 years (32%), single (48%) and unemployed (34%). Participants partook in a 24-week DBT-ST intervention delivered by DBT therapists. Outcome measures included the Difficulties in Emotion Regulation Scale (DERS), the DBT Ways of Coping Checklist (DBT-WCCL) and the Five Facet Mindfulness Questionnaire (FFMQ). Measures were administered at pre-intervention, at the end of each skills module, and at post-intervention. Results Significant reductions in emotion dysregulation (DERS) and dysfunctional coping (DBT-WCCL) scores were reported from pre- to post-intervention (p < .001). A significant increase in mindfulness scores (FFMQ) and DBT skill use (DBT-WCCL) was also observed (p < .001). However, the drop-out rate was high (49% at post-intervention). Discussion The results of this uncontrolled study suggest that a standalone 24-week DBT-ST intervention may have a beneficial impact in terms of a reduction in emotion dysregulation and dysfunctional coping, and an increase in mindfulness and DBT skills use in patients with BPD/ emerging BPD traits who are not currently engaging in self-harm. Adequately powered randomised controlled trials are required to determine treatment efficacy in comparison to standard DBT for this population.